A linguagem visual da James Harper’s Illuminated and New Pictorial Bible: uma articulação popular metodista do afeto religioso e da sensibilidade social - Alexandrini, Ana Beatriz de Carvalho dos Santos (2022)
In this dissertation, we will work with the Protestant visual language, present in James Harper's Illuminated and New Pictorial Bible, an illustrated family Bible, in English, created, edited and marketed by the Harper brothers, lay people of the Methodist Episcopal Church, who lived in the United States during the 19th century. Using the iconological method of Erwin Panofsky, we will look for traces in the illustrations of a possible existence of a functionality in the use of images in the Bible of social sensitivity and religious affection, considering that, it is a great work, with approximately , 1600 illustrations in woodcut molds. The justification for this research is the need to better understand the evangelical visual languages used in past times, including within this denomination that belongs to Brazil, in Mission Protestantism, in the case of this research, the Methodist Church. In order to do so, we will seek to know briefly, a little of the history that involves the production of this Bible, both of its creators and of the Methodist and Protestant predecessors, in the use of visual language in their cults, rites and social media (AU)